2016
DOI: 10.1093/cz/zow096
|View full text |Cite
|
Sign up to set email alerts
|

Genetic load in marine animals: a review

Abstract: Marine invertebrates and fish are well known for their remarkable genetic diversity, which is commonly explained by large population size and the characteristic dispersive nature of their early, planktonic life history. Other potential sources of diversity in marine animals, such as a higher mutation rate, have been much less considered, though evidence for a high genetic load in marine bivalves has been accumulating for nearly half a century. In this review, I examine evidence for a higher genetic load in mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 130 publications
(200 reference statements)
2
79
1
Order By: Relevance
“…However, several empirical evidences from molecular evolution and population genetics studies have 543 also shown that oysters have among the highest segregating loads of deleterious mutations observed in 544 marine invertebrates (Sauvage et al, 2007, Plough, 2016. This may be due to a high variance in 545 reproductive success (sweepstake effect) and population size fluctuations 546 Harrang, et al 2013;Hedgecock 1994;Hedgecock and Pudovkin 2011;Plough 2016). We are lacking 547 theoretical predictions on the effect of linked selection in a species with skewed offspring distribution, 548 but the effect is likely more genome-wide during favorable sweepstake events than it is in the standard 549 Wright-Fisher model.…”
Section: Divergence History 424mentioning
confidence: 99%
“…However, several empirical evidences from molecular evolution and population genetics studies have 543 also shown that oysters have among the highest segregating loads of deleterious mutations observed in 544 marine invertebrates (Sauvage et al, 2007, Plough, 2016. This may be due to a high variance in 545 reproductive success (sweepstake effect) and population size fluctuations 546 Harrang, et al 2013;Hedgecock 1994;Hedgecock and Pudovkin 2011;Plough 2016). We are lacking 547 theoretical predictions on the effect of linked selection in a species with skewed offspring distribution, 548 but the effect is likely more genome-wide during favorable sweepstake events than it is in the standard 549 Wright-Fisher model.…”
Section: Divergence History 424mentioning
confidence: 99%
“…Individual condition will depend on the presence of both beneficial alleles across the genome, as well as the existence of deleterious alleles in the form of 'mutation load'. All life is subject to the perpetual risk of mutation load: the accumulation of imperfect genetic variants that exist in all lineages, and which reduces net fitness in a population below that of one which is hypothetically load-free and perfectly adapted to its environment (Haldane 1937;Muller 1950;Crow 1958;Simmons and Crow 1977;Agrawal and Whitlock 2012;Plough 2016;Simons and Sella 2016). Natural selection will remove deleterious mutations with detectable phenotypic effects, however, mutations of weak effect are much harder to eliminate, but can sum across multiple loci and individuals to create a significant total genetic load (Fisher 1930;Haldane 1937;Muller 1950;Kimura et al 1963;Felsenstein 1974;Charlesworth et al 1993;Lande 1994;Lynch et al 1995;Crow 1997).…”
Section: Introductionmentioning
confidence: 99%
“…). Marine species, especially oysters and other invertebrates, appear to have higher loads of deleterious mutations than terrestrial species (Launey & Hedgecock ; Plough & Hedgecock ; Plough ; Plough et al . ), so inbreeding depression is likely to be severe in these small hatchery‐propagated populations.…”
Section: Discussionmentioning
confidence: 99%